The readiness of smart office interior implementation in Malaysia - Halim, Nor Hafiza; Awang, Arita Hanim; Ahmad, Noraini; Ab Jalil, Nurlelawati; Ab Rahman, Syakir Amir; Hj. Mohd. Noor, Norzailawati; Sapian, Abdul Razak; Ahmad, Norfazillah (Alanya University, Turkey, 2022)
Covid-19 is the most trending indication that digitalization and generation Z's arrival into the labour supply -drive companies to reconsider traditional office space. Smart office interior is the future of today, which involves using technology to facilitate productive and effective working. As a consequence of this occurrence, researchers and industry professionals are focusing on the research and development of smart office interiors. This study aimed to emphasize the readiness of smart office interiors and the potential consequences of implementing smart office interiors in Malaysia. Descriptive statistics were obtained using the questionnaire survey responses from various industrial sectors. This study indicated the corpus of knowledge on Malaysia's current readiness for smart office interiors adoption. To summarise, Malaysia's everyday situations show that more strategies are needed to be introduced in Malaysia to reap the benefits of the smart office revolution, which will save energy, time, and money.